Porous hollow fiber membrane

JP2025007450APending Publication Date: 2025-01-17ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023108858
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Benefits of technology

【0014】 本発明によれば、無機物や有機物を含有する液体の処理に好適な、耐擦過性、高い透水性能、耐圧縮強度を有する多孔性中空糸膜を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007450000001_ABST
    Figure 2025007450000001_ABST
Patent Text Reader

Abstract

To provide a porous hollow fiber membrane which is excellent not only in scratch resistance but also in water permeability, and furthermore is excellent in mechanical strength.SOLUTION: A porous hollow fiber membrane 1 in an approximately cylinder shape is formed of thermoplastic resin, and includes a plurality of uneven parts 3, 4 continuously extending in a longer direction of the hollow fiber membrane on an outer circumferential part and inner circumferential part. The uneven parts include recess parts and convex parts alternately formed along a circumferential direction of the hollow fiber membrane.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a porous hollow fiber membrane. Specifically, the present invention relates to a porous hollow fiber membrane having projections and recesses on its outer and inner peripheries. [Background technology]

[0002] In recent years, porous membranes such as ultrafiltration membranes and microfiltration membranes have been used in a wide range of fields, including the recovery of electrocoating paint, the removal of fine particles from ultrapure water, the production of pyrogen-free water, the concentration of enzymes, the sterilization and clarification of fermentation liquid, and the treatment of drinking water, sewage, and wastewater. In particular, porous hollow fiber membranes are widely used because they have a high membrane packing density per unit volume and can make treatment equipment more compact.

[0003] When various liquids to be treated are filtered using a porous hollow fiber membrane, a major problem is that some of the inorganic and / or organic matter contained in the liquid to be treated is adsorbed, blocked or deposited in the membrane pores or on the membrane surface, resulting in a decrease in water permeability due to so-called fouling.

[0004] As a method for suppressing such fouling phenomenon, Patent Document 1 discloses a physical cleaning method (so-called air scrubbing) in which air is introduced into a hollow fiber membrane container to vibrate the liquid in the container and remove fine particles attached to the hollow fiber membrane surface. Not only in the case-type module of Patent Document 1, but also in non-cased type (submerged type) modules often used in MBR (membrane bioreactor), a method of suppressing fouling by introducing air from the bottom of the module is generally used. However, while this method can effectively suppress membrane fouling, it is prone to the phenomenon in which the pores on the outer surface of the membrane are blocked by contact between membranes, that is, the so-called "abrasion", and as a result, there is a problem that the water permeability of the membrane decreases during long-term operation.

[0005] Membranes with special shapes have also been disclosed to enhance the effect of this air scrubbing. Patent Document 2 discloses a membrane in which hollow fibers are provided with meandering crimps to suppress a decrease in membrane area due to contact between hollow fibers and a decrease in treatment performance due to liquid retention.

[0006] Patent Document 3 discloses a film having irregularities on the outer surface side, which is capable of suppressing abrasion. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Unexamined Patent Publication No. 60-19002 [Patent Document 2] Japanese Patent Application Publication No. 57-194007 [Patent Document 3] International Publication No. 2010 / 063772 Summary of the Invention [Problem to be solved by the invention]

[0008] However, it is difficult to say that the films disclosed in Patent Documents 2 and 3 provide sufficient effects in terms of improving the air scrubbing effect and suppressing abrasion.

[0009] In the shape disclosed in Patent Document 2, the crimp period in the longitudinal direction of the hollow fiber is long, ranging from several mm to several tens of mm, making it impossible to control the flow of liquid over the entire membrane surface. As a result, uneven fouling occurs, and there is a problem in that a sufficient effect cannot be obtained. Furthermore, the angle at which the membranes come into contact with each other can change, or the membranes can bend and come into contact due to air scrubbing, so the effect of preventing abrasion is small and there is also the problem that the decrease in water permeability cannot be sufficiently prevented.

[0010] In addition, although the membrane disclosed in Patent Document 3 suppresses abrasion, the inner surface side of the hollow fiber does not have the same unevenness as conventional membranes, and the water permeability of the actual liquid is not sufficient. In addition, since external pressure filtration was assumed, no improvement in water permeability could be expected when using internal pressure filtration, so further improvements were desired.

[0011] An object of the present invention is to provide a porous hollow fiber membrane which is excellent not only in abrasion resistance but also in water permeability and mechanical strength. [Means for solving the problem]

[0012] The present inventors conducted extensive research to solve the above-mentioned problems with a roughly cylindrical porous hollow fiber membrane made of a thermoplastic resin, and as a result, they discovered that having a plurality of projections and recesses extending continuously in the longitudinal direction of the hollow fiber membrane on the outer and inner peripheral portions is extremely important for improving abrasion resistance and real liquid performance, which led to the present invention.

[0013] That is, the present invention is as follows. (1) A substantially cylindrical porous hollow fiber membrane made of a thermoplastic resin, A porous hollow fiber membrane, characterized in that the outer and inner circumferential portions have a plurality of projections and recesses extending continuously in the longitudinal direction of the hollow fiber membrane, and the projections and recesses are alternately formed along the circumferential direction of the hollow fiber membrane. (2) The porous hollow fiber membrane according to (1), characterized in that the apex of the convex portion of the inner periphery is located on a line connecting the apex of the concave portion of the outer periphery and the center of the hollow fiber membrane. (3) The porous hollow fiber membrane according to (1) or (2), characterized in that the ratio of the height of the projections and recesses in the outer circumferential portion to the height of the projections and recesses in the inner circumferential portion (height of the projections and recesses in the outer circumferential portion / height of the projections and recesses in the inner circumferential portion) is 1.0 or more and 20 or less. (4) The porous hollow fiber membrane according to any one of (1) to (3), characterized in that a ratio of an inner diameter of the recesses in the inner circumferential portion / 2 to an unevenness height in the inner circumferential portion (unevenness height / (inner diameter of the recesses / 2)×100%) is 1.0 to 33%. (5) The porous hollow fiber membrane according to any one of (1) to (4), wherein the height of the projections and recesses on the inner peripheral portion is 1 to 110 μm and the height of the projections and recesses on the outer peripheral portion is 1 to 320 μm. (6) The porous hollow fiber membrane according to any one of (1) to (5), wherein the width of the irregularities on the outer periphery is 1 to 500 μm. (7) The porous hollow fiber membrane according to any one of (1) to (6), wherein the width of the irregularities on the inner periphery is 1 to 500 μm. (8) The porous hollow fiber membrane according to any one of (1) to (7), wherein a value obtained by dividing the surface porosity of the recesses of the inner circumferential portion by the surface porosity of the protrusions of the inner circumferential portion is 1.01 to 2.00. (9) The porous hollow fiber membrane according to any one of (1) to (8), wherein the outer peripheral portion and the inner peripheral portion have 1 to 200 projections and recesses in the circumferential direction of the hollow fiber membrane. (10) The porous hollow fiber membrane according to any one of (1) to (9), wherein the thermoplastic resin contains a fluororesin or a polyolefin resin as a main component. (11) The porous hollow fiber membrane according to (10), characterized in that the fluororesin contains at least one selected from the group consisting of polyvinylidene fluoride resin (PVDF), chlorotrifluoroethylene resin, tetrafluoroethylene resin, ethylene-tetrafluoroethylene copolymer (ETFE), ethylene-monochlorotrifluoroethylene copolymer (ECTFE), hexafluoropropylene resin, and mixtures of these resins. Effect of the Invention

[0014] According to the present invention, it is possible to obtain a porous hollow fiber membrane having abrasion resistance, high water permeability, and compressive strength suitable for treating liquids containing inorganic or organic substances. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a perspective view showing a schematic diagram of a porous hollow fiber membrane according to an embodiment of the present invention. [Diagram 2]2 is an enlarged cross-sectional view showing a schematic diagram of irregularities formed on the outer periphery of the porous hollow fiber membrane of the present embodiment. FIG. [Diagram 3] FIG. 1 is a diagram for explaining the length from the center of the hollow fiber membrane to the apex of the convex portion, the length from the center of the hollow fiber membrane to the bottom of the concave portion, and the center-to-center distance between adjacent porous hollow fiber membranes for the porous hollow fiber membrane of this embodiment. [Figure 4] FIG. 2 is a schematic diagram for explaining an isotropic three-dimensional mesh structure. [Diagram 5] FIG. 2 is a schematic diagram for explaining a spherical structure. [Figure 6] FIG. 2 is a diagram showing a schematic diagram of an example of a production apparatus used for producing a porous hollow fiber membrane of an embodiment. [Figure 7] FIG. 1 is a diagram showing a schematic diagram of an example of a filtration module using the porous hollow fiber membrane of the present embodiment. [Figure 8] 1 is an image of a cross section perpendicular to the extension direction of the porous hollow fiber membrane obtained in Example 1, observed using an electron microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, a detailed description will be given of an embodiment of the present invention (hereinafter, referred to as the present embodiment). Note that the present invention is not limited to the following embodiment, and can be modified in various ways within the scope of the present invention.

[0017] The porous hollow fiber membrane according to this embodiment is made of a thermoplastic resin and is a substantially cylindrical porous hollow fiber membrane having an opening in the center. As shown in FIG. 1, the porous hollow fiber membrane of this embodiment has a plurality of projections and recesses extending continuously in the longitudinal direction of the hollow fiber membrane. Here, the "outer periphery" of the porous hollow fiber membrane in this embodiment means the outer periphery when viewed in a cross section perpendicular to the extension direction of the porous hollow fiber membrane, i.e., the outer surface of the porous hollow fiber membrane. Also, the "inner periphery" of the porous hollow fiber membrane in this embodiment means the outer periphery when viewed in a cross section perpendicular to the extension direction of the porous hollow fiber membrane, i.e., the inner surface of the porous hollow fiber membrane. Furthermore, "unevenness extending continuously in the longitudinal direction of the hollow fiber membrane" means that, as shown in Figure 1, when viewed in any cross section perpendicular to the extension direction of the porous hollow fiber membrane, the unevennesses 3 and 4 on the outer and inner peripheral parts respectively have approximately the same shape, and the recesses 3A and 4A and the protrusions 3B and 4B extend along the extension direction of the porous hollow fiber membrane.

[0018] In the porous hollow fiber membrane of this embodiment, the outer and inner peripheral portions have a plurality of projections and recesses 3, 4 that extend continuously in the longitudinal direction of the hollow fiber membrane, which has the following effects: (1) high real liquid permeability can be exhibited by turbulent flow on the outer and inner surfaces of the membrane during filtration, (2) the points where membranes are likely to come into contact with each other are limited to the projections, thereby preventing a decrease in permeability due to abrasion, (3) the surface area during filtration is increased, further improving real liquid permeability, and (4) high real liquid permeability can be exhibited regardless of whether filtration is performed under external pressure or internal pressure.

[0019] Furthermore, the concave and convex portions included in the unevenness refer to, in a cross section perpendicular to the extension direction of the porous hollow fiber membrane, in the case of the outer periphery of the hollow fiber membrane, as shown in Figure 2, a portion that is convex outward (a region whose center of curvature is inside the outer periphery of the porous hollow fiber membrane) is called convex portion 3A, and a portion that is concave outwardly from the outer periphery of the membrane (a region whose center of curvature is outside the outer periphery of the porous hollow fiber membrane) is called concave portion 3B. In the porous hollow fiber membrane of this embodiment, as shown in Fig. 1, the multiple projections and recesses 3, 4 extending continuously in the longitudinal direction of the hollow fiber membrane are alternately formed along the circumferential direction of the hollow fiber membrane, thereby making it possible to more reliably achieve the effects (1) to (4) described above. Incidentally, even if there is no concave portion 3A or convex portion on the outer periphery, concaves and convexes are formed on the outer periphery, for example, when there is no convex portion, concaves may be adjacent to each other at their peaks, and in this case, a pointed portion having a mountain-like cross section is formed between the concaves, but this pointed portion is not a region with an inner center of curvature and therefore does not become a convex portion. On the other hand, when there is no concave portion, concaves are adjacent to each other at their valleys, and a pointed groove is formed between the convex portions, but this groove is not a region with an outer center of curvature and therefore does not become a concave portion.

[0020] Similarly, in the case of the inner circumference of the hollow fiber membrane, the portion that is convex inward from the inner circumference of the membrane (the region where the center of curvature is inside the inner circumference of the porous hollow fiber membrane) is called convex portion 4A, and the portion that is concave inward from the inner circumference of the membrane (the region where the center of curvature is outside the inner circumference of the porous hollow fiber membrane 1) is called concave portion 4B.

[0021] Next, the irregularities formed on the outer periphery of the porous hollow fiber membrane will be described. Incidentally, although FIG. 2 is a diagram for explaining the unevenness 3 on the outer periphery, the unevenness 4 formed on the inner periphery can be understood in a similar manner.

[0022] The height and width of the irregularities and the number of irregularities in the outer periphery of the membrane can be appropriately changed depending on the outer periphery length of the hollow fiber membrane and the height and width of the irregularities, but it is preferable for the effects of the present invention to be fully exhibited when they are within the following ranges.

[0023] The height of the irregularities in the outer periphery is preferably 1 μm or more and 320 μm or less. Here, the height of the irregularities in the outer periphery refers to the length from the surface 3C of the circumference connecting the bottoms of the recesses 3B to the apex of the protrusion 3A, as shown in Fig. 2, and can be expressed as the sum of the height Ha of the region forming the protrusion 3A and the depth Hb of the region forming the recess 3B, as shown in Fig. 2. If the unevenness height (Ha+Hb) is 1 μm or more, high cleaning recovery and abrasion resistance can be exhibited at a higher level, and if the unevenness height (Ha+Hb) is 320 μm or less, membranes can be integrated at a practical packing rate when modularized. From the same viewpoint, the unevenness height (Ha+Hb) is more preferably 5 μm or more and 200 μm or less, and further preferably 10 μm or more and 160 μm or less.

[0024] The height of the projections and recesses on the inner circumferential portion is preferably 1 μm or more and 110 μm or less. Note that the height of the projections and recesses on the inner circumferential portion, like the height on the outer circumferential portion, refers to the length from the surface of the circumferential portion to the apex of the projection 3A. If the height of the unevenness of the inner periphery is 1 μm or more, the surface area of ​​the outer periphery and the inner periphery is improved, that is, the surface area contributing to filtration is improved, so that higher filtration performance can be expressed. In addition, when used in internal pressure filtration, the effect of scraping off membrane dirt attached to the surface is improved, and similarly the filtration performance is further improved. On the other hand, if the height of the unevenness of the inner periphery is 110 μm or less, the turbulent effect on the inner surface side can be maintained, and in the case of internal pressure filtration, the effect of scraping off membrane dirt can also be well maintained. In addition, when the membrane is deformed due to pressure from the outer surface, etc., the contact between the convex parts facing each other can be suppressed. From the same viewpoint, the height of the unevenness of the inner periphery is preferably 5 μm or more and 100 μm or less, more preferably 10 μm or more and 90 μm or less.

[0025] Furthermore, the ratio of the height of the unevenness of the outer periphery to the height of the unevenness of the inner periphery (height of the unevenness of the outer periphery / height of the unevenness of the inner periphery) is preferably 1.0 or more and 20 or less. When the ratio of the height of the unevenness of the outer periphery to the height of the unevenness of the inner periphery) is 1.0 or more and 20 or less, the balance of the height of the unevenness of the outer periphery and the inner periphery is good, the moldability is stable, and the water permeability, abrasion resistance, and mechanical strength can be achieved while suppressing the use of excessive resin. From the same viewpoint, the ratio of the height of the unevenness of the outer periphery to the height of the unevenness of the inner periphery) is preferably 2.0 or more and 15 μm or less, and more preferably 2.0 or more and 10 or less.

[0026] In addition, the ratio of the height of the unevenness of the inner periphery to the inner diameter / 2 of the recess of the inner periphery (height of unevenness / (inner diameter of recess / 2)×100%) is preferably 1.0 to 33%. If the ratio of the inner diameter / 2 of the recess of the inner periphery (height of unevenness / (inner diameter / 2)) is 1.0% or more, the surface area of ​​the inner periphery is improved, that is, the surface area contributing to filtration is improved, so that higher filtration performance can be expressed. In addition, when used in internal pressure filtration, the effect of scraping off the membrane dirt attached to the surface of the inner periphery is improved, and the filtration performance is also improved. On the other hand, if the ratio of the inner diameter / 2 of the recess of the inner periphery (height of unevenness / (inner diameter of recess / 2)×100%) is 33% or less, the turbulence effect on the inner surface side can be maintained, and in the case of internal pressure filtration, the effect of scraping off the membrane dirt can be maintained. In addition, it is also possible to suppress contact between the convex parts facing each other when the membrane is deformed due to pressure from the outer surface, etc. From the same viewpoint, the ratio of the inner diameter of the recessed portion of the inner periphery / 2 (height of the recessed portion / (inner diameter of the recessed portion / 2)×100%) is preferably 1.0% or more and 30% or less, and more preferably 1.0% or more and 25% or less.

[0027] The width of the unevenness of the outer circumferential portion is preferably 1 to 500 μm. Here, the width of the unevenness of the outer circumferential portion refers to the width of the region forming the protrusions 3A and the recesses 3B, and can be expressed as the sum of the width Wa of the protrusions 3A and the width Wb of the recesses 3B of the porous hollow fiber membrane 1, as shown in FIG. In actual measurement, the distance between the bottoms of adjacent recesses can be measured by a straight line. If the width of the unevenness of the outer periphery is 1 μm or more, the projections will not be crushed when performing external pressure filtration, and the abrasion of the recesses can be sufficiently suppressed. On the other hand, if the width of the unevenness of the outer periphery is 500 μm or less, it is possible to effectively suppress the adhesion and deposition of inorganic and / or organic matter on the tip of the projections due to the complex flow of fluid near the membrane surface. From the same viewpoint, the width of the unevenness of the outer periphery is more preferably 5 μm or more and 400 μm or less, and even more preferably 10 μm or more and 350 μm or less.

[0028] The width of the unevenness of the inner periphery is preferably 1 to 500 μm. Here, the width of the unevenness of the inner periphery refers to the width of the region forming the convex portion 4A and the concave portion 4B. If the width of the unevenness of the inner periphery is 1 to 500 μm, the turbulent flow effect on the inner surface side is maintained, and in the case of internal pressure filtration, the effect of scraping off membrane dirt is maintained. In addition, if the width of the unevenness of the inner periphery is 1 μm or more, it is possible to suppress contact between adjacent convex portions when the membrane is deformed by pressure from the outer surface, etc. From the same viewpoint, the width of the unevenness of the inner periphery is preferably 10 μm or more and 300 μm or less, more preferably 20 μm or more and 300 μm or less.

[0029] Furthermore, it is preferable that the width Wb of the recess 3B of the outer periphery is equal to or less than the maximum width Wa of the protrusion 3A of the outer periphery, and the height Ha of the protrusion 3A of the outer periphery is equal to or less than the depth Hb of the recess 3B. When the protrusion 3A and the recess 3B of the outer periphery satisfy the above-mentioned relationship, the apex of the protrusion 3A of the outer periphery is prevented from hitting the bottom of the recess 3B of the outer periphery between adjacent porous hollow fiber membranes, and the water permeability of the bottom of the recess 3B due to rubbing can be prevented from decreasing, so that the water permeability of the porous hollow fiber membrane can be stably realized. Furthermore, regarding the retention of the moisturizing agent, the above-mentioned shape reduces the effect of the moisturizing agent on the membrane surface being removed by rubbing between the membranes during transportation, etc., so that higher dry resistance can be exhibited.

[0030] The number of uneven stripes in the circumferential direction of the outer periphery of the porous hollow fiber membrane of this embodiment is preferably 1 to 300. If the number of uneven stripes on the outer periphery is 1 or more, a complex flow can be generated in the vicinity of the membrane surface, making it possible to prevent adhesion and deposition of inorganic and / or organic substances on the membrane surface, and if the number of uneven stripes on the outer periphery is 300 or less, protrusions can be formed with high precision on the outer periphery of the hollow fiber porous membrane. From the same viewpoint, the number of uneven stripes on the outer periphery is more preferably 8 to 200, and even more preferably 12 to 150.

[0031] The number of projections and recesses on the inner periphery of the porous hollow fiber membrane of this embodiment is preferably 1 to 200. If the number of projections and recesses on the inner periphery is 1 or more, a complex flow is generated near the membrane surface, and a turbulent flow effect on the inner surface side is exhibited. If the number of projections and recesses on the inner periphery is 200 or less, protrusions can be formed with high precision on the inner periphery of the hollow fiber porous membrane. More preferably, the number is 8 to 160, and even more preferably, the number is 12 to 100.

[0032] In the porous hollow fiber membrane of this embodiment, with regard to the positional relationship between the projections and recesses of the outer peripheral portion and the inner peripheral portion, it is preferable that the apex of the recess 4B of the inner peripheral portion is located on a line connecting the center C of the hollow fiber membrane to the apex of the projection 3A of the outer peripheral portion, as shown in Fig. 1. The apex of the recess 4B of the inner peripheral portion is located on a line connecting the center C of the hollow fiber porous membrane to the apex of the projection 3A of the outer peripheral portion when the deviation ratio of the apex of the bottom 4B of the recess of the inner peripheral portion is within 30% when connecting the apex of the projection 3A of the outer peripheral portion from the center C of the hollow fiber porous membrane. In this case, the deviation ratio is expressed as follows: Deviation ratio = (angle between the line segment connecting the center and the apex of the convex part on the outer periphery and the line segment connecting the center and the bottom of the concave part on the inner periphery) / (360°C / number of threads) x 100 If the apex of the inner peripheral recess 4B is located on a line connecting the center C of the hollow fiber porous membrane to the apex of the outer peripheral protrusion 3A, the compressive strength and burst strength can be increased. It is presumed that the strength can be increased by suppressing stress concentration when pressure is applied from the outside or inside.

[0033] The shape of the outer circumferential portion and the inner circumferential portion of the unevenness is not particularly limited, and various shapes can be mentioned.

[0034] Furthermore, as shown in FIG. 3, for the unevenness on the outer peripheral portion of the porous hollow fiber membrane of the present embodiment, the sum (r1 + r2) of the length r1 from the center C of the porous hollow fiber membrane (1A, 1B) to the apex of the convex portion 3A and the length r2 from the center C of the porous hollow fiber membrane 1 (1A, 1B) to the bottom of the concave portion 3B is preferably smaller than the center-to-center distance L between adjacent porous hollow fiber membranes 1A and 1B (r1 + r2 < L). Thereby, even when adjacent porous hollow fiber membranes 1 rub against each other due to vibration or the like, it is possible to prevent the apex of the convex portion 3A from hitting the bottom of the concave portion 3B. Therefore, the abrasion resistance of the porous hollow fiber membrane 1 is enhanced, the decrease in the water permeability of the bottom of the concave portion 3B due to abrasion is prevented, and as a result, the decrease in the water permeability of the porous hollow fiber membrane is suppressed.

[0035] The length from the center C of the porous hollow fiber membrane to the apex of the convex portion 3A, the length r2 from the center C of the porous hollow fiber membrane to the bottom of the concave portion 3B, and the center-to-center distance L of the porous hollow fiber membrane can be measured as follows. First, prepare microscope photographs of two cross-sections of the hollow fiber membrane. The magnification of the photograph may be any magnification as long as the entire cross-section of the membrane can be seen. The cross-section photographs of the two membranes may use the same photograph, or if the membranes have a substantially similar structure in the longitudinal direction, photographs of other locations may be used. Paste cardboard on the back sides of these two photographs, cut them along the outer peripheral portion of the membrane with scissors, and use them as substitutes for the actual membrane cross-section. The center-to-center distance is adopted with the intersection of the major axis and the minor axis of the inner diameter as the center point of each membrane cross-section. While rotating the two membrane cross-sections (the ones with the photographs cut out), determine the arrangement where the distance between the two center points is the shortest, and then actually measure the center-to-center distance with a ruler. Then, convert it to the actual distance according to the magnification of the photograph to obtain the center-to-center distance L. Further, measure the length r1 from the center point to the convex portion (i.e., the point farthest from the center point) and the length r2 from the center point to the concave portion (the point closest to the outer peripheral portion from the center point) on the same photograph, and compare the length of the sum of the center-to-center distance L, r1, and r2. The above measurement can be preferably performed when the membrane is small. If there are no problems such as the hollow fiber membrane being small and difficult to handle, it is also possible to preferably perform the measurement on a microscope by thinly cutting two actual membrane cross-sections.

[0036] The value (L / (r1+r2)) obtained by dividing the center-to-center distance L between adjacent hollow fiber membranes by the sum of the length r1 to the apex of the protrusion 3A and the length r2 to the bottom of the recess 3B is preferably 1.01 to 1.50, more preferably 1.03 to 1.25, and most preferably 1.05 to 1.15. If the value obtained by dividing the center-to-center distance L by the sum of r1 and r2 is 1.50 or less, the fiber bundle packed in the membrane module will not become too thick, and as a result, an economically sufficient membrane packing rate can be ensured. Furthermore, when the above relationship is satisfied in a cross section perpendicular to the longitudinal direction at any position in the longitudinal direction of the porous hollow fiber membrane, the abrasion resistance and water permeability of the porous hollow fiber membrane are significantly improved.

[0037] In addition, in order to improve the strength of the porous hollow fiber membrane of this embodiment, the openings inside the porous hollow fiber membrane can also be structured to have a porous support layer and / or a support such as a braided cord on the inner surface side. Furthermore, when the porous hollow fiber membrane of this embodiment is a multilayer membrane, the thickness of the outermost layer having the unevenness may be constant, and the thickness of the region in which the unevenness is formed may be greater or smaller than the thickness of the region in which the unevenness is formed.

[0038] The thermoplastic resin (thermoplastic polymer) constituting the porous hollow fiber membrane of this embodiment is not particularly limited as long as it is elastic and does not show plasticity at room temperature, but shows plasticity when heated appropriately. The thermoplastic resin used as the material is a resin that can be molded into a porous hollow fiber membrane by heating, and undergoes a reversible change to return to its original elastic body when cooled and the temperature drops, and has the property of not causing chemical changes such as molecular structure during this time (Chemical Encyclopedia Editorial Committee, Chemical Encyclopedia 6, Condensed Edition, Kyoritsu Shuppan, pp. 860 and 867, 1963).

[0039] Examples of the thermoplastic resin include those described in the section on thermoplastics (pages 1069-1125) of Chemical Products No. 14705 (The Chemical Daily, 2005) and those described in the section on thermoplastics (pages 809-810) of Chemical Handbook, Applied Edition, 3rd Revised Edition (edited by the Chemical Society of Japan, Maruzen, 1980). Specific examples include polyethylene, polypropylene, polyvinylidene fluoride, ethylene-vinyl alcohol copolymer, polyamide, polyetherimide, polystyrene, polysulfone, polyvinyl alcohol, polyphenylene ether, polyphenylene sulfide, cellulose acetate, polyacrylonitrile, etc. Among them, polyethylene, polypropylene, polyvinylidene fluoride, ethylene-vinyl alcohol copolymer, polyvinyl alcohol, etc., which have crystallinity, can be preferably used in terms of strength expression. Furthermore, among these crystalline thermoplastic resins, hydrophobic crystalline thermoplastic resins such as polyolefins such as polyethylene and polypropylene, which are hydrophobic and therefore have high water resistance and can be expected to have durability in filtering normal aqueous liquids, and polyvinylidene fluoride can be more preferably used. Furthermore, among these hydrophobic crystalline thermoplastic resins, polyvinylidene fluoride, which has excellent chemical durability such as chemical resistance, can be particularly preferably used. Examples of polyvinylidene fluoride include vinylidene fluoride homopolymers and vinylidene fluoride copolymers with a vinylidene fluoride ratio of 50 mol% or more. Examples of vinylidene fluoride copolymers include copolymers of vinylidene fluoride and one or more selected from tetrafluoroethylene, hexafluoropropylene, trifluorochloroethylene, and ethylene. As polyvinylidene fluoride, vinylidene fluoride homopolymers are most preferable. As a polymerization method for vinylidene fluoride resins, both emulsion polymerization products and suspension polymerization products can be preferably used.

[0040] In addition, the porous hollow fiber membrane according to the present embodiment is formed by a porous membrane having an isotropic three-dimensional mesh structure. Isotropic means that the change in pore size in the membrane thickness direction and the membrane longitudinal direction is small, and the structure is homogeneous and does not contain macrovoids. This structure is clearly different from the structure oriented in the membrane longitudinal direction, which is typical of the stretching hole opening method, and the structure containing macrovoids and having a large change in pore size in the membrane cross-sectional direction, which is often seen in the non-solvent induced phase separation method. By making the structure homogeneous in this way, the surfaces of both the recessed and protruding parts can be efficiently used during filtration. In addition, since weak parts such as macrovoids are unlikely to occur, it is possible to increase the mechanical strength such as pressure resistance while maintaining the water permeability of the porous hollow fiber membrane.

[0041] Isotropy is a state in which two conditions are satisfied: (1) there are no voids with a diameter of 10 μm or more in the cross section in the circumferential direction of the membrane, and (2) the ratio of (pore size in the longitudinal direction of the membrane) / (pore size in the membrane thickness direction) (hereinafter referred to as the degree of orientation) in the cross section in the longitudinal direction of the membrane is small. If there are no voids and the degree of orientation is in the range of 0.25 to 4.0, it can be said to be isotropic. When the membrane has such a degree of orientation, the porous hollow fiber membrane 1 can exhibit high water permeability and durability as described above.

[0042] The three-dimensional mesh structure referred to here is a structure in which the resin forms countless columns, which are joined to each other at both ends to form a three-dimensional structure. In a three-dimensional mesh structure, the resin almost entirely forms columns, and the countless resin lumps seen in so-called spherical structures are hardly seen. The voids in the three-dimensional mesh structure are surrounded by thermoplastic resin columns, and each part of the voids is connected to each other. In this way, most of the resin used forms columns that can contribute to the strength of the hollow fiber membrane, making it possible to form a membrane with high strength. Chemical resistance is also improved. The reason for the improvement in chemical resistance is not clear, but it is believed that the resin contributes to strength. This is probably because there are many columns that can be formed, and even if some of the columns are damaged by chemicals, the strength of the entire film is not significantly affected. On the other hand, in the spherical structure, the resin is concentrated in clumps, so the number of columns is relatively small and the strength is low. Therefore, it is thought that if some of the columns are damaged by chemicals, the strength of the entire film is easily affected. By making such an isotropic three-dimensional mesh structure, it is possible to maintain high strength even in the convex parts, and as a result, the convex parts do not deform during use, and the uneven shape can be maintained even during long-term use. A schematic diagram of an isotropic three-dimensional mesh structure is shown in Figure 4. In Figure 4, it can be seen that voids b are formed by the joining of columns a. For reference, a schematic diagram of a spherical structure is shown in Figure 5. In Figure 5, it can be seen that spherulites c are partially dense, and the gaps between the dense parts of the spherulites c are voids d.

[0043] Furthermore, as a result of investigations by the inventors, it has been found that in the porous hollow fiber membrane of this embodiment, it is preferable for the surface porosity of the recesses in the outer periphery to be higher than the surface porosity of the protruding portions in the outer periphery, both in terms of achieving high filtration performance and in terms of preventing a decrease in water permeability due to abrasion during long-term use. The recesses referred to here are regions whose center of curvature is on the outside of the porous hollow fiber membrane, as described above, and are regions 3B indicated by arrows in FIG. 2. The peripheral convex portions 3A are regions whose center of curvature is on the inside of the porous hollow fiber membrane 1, as described above, and are regions sandwiched between the peripheral recesses 3B in FIG. 2. The reason why the surface porosity of the peripheral recesses 3B is higher than that of the convex portions 3A suppresses the decrease in water permeability is unclear, but it is considered important that the porosity of the recesses 3B is higher than that of the convex portions 3A to not only improve the porosity of the entire membrane surface, but also that the membrane surface is not used for filtration at the same time, and the surface used for filtration shifts over time from the recesses, which have higher porosity, to the convex portions, which have relatively lower porosity.

[0044] As described above, the recesses 3B have a surface that is highly recoverable by air scrubbing or shearing, and is difficult to be scratched. Therefore, it is considered preferable that the recesses have a higher porosity, i.e., a high water permeability, so that the membrane surface as a whole can maintain a high water permeability for a long period of time. The ratio of the surface porosity of the recesses to the surface porosity of the protrusions is preferably 1.01 or more and 2.00 or less. If it is 1.01 or more, high water permeability can be achieved, and if it is 2.00 or less, not only the recesses but also the protrusions are used for filtration, so that the effect of improving the external surface area due to the unevenness is also taken into account, and high water permeability can be achieved. More preferably, it is 1.08 or more and 1.80 or less, and even more preferably, it is 1.10 or more and 1.50 or less.

[0045] The porosity of each of the uneven portions may be appropriately determined depending on the purpose and is not particularly limited, but from the viewpoint of filtration stability of the liquid to be treated containing suspended solids, etc., it is preferably 20% or more, more preferably 23% or more, and even more preferably 25% or more. From the viewpoint of improving the mechanical strength of the surface portion, the porosity is preferably 80% or less, more preferably 70% or less, and even more preferably 60% or less.

[0046] Furthermore, as a result of the study by the present inventors, in the porous hollow fiber membrane, the surface porosity of the recesses 3B in the inner periphery is preferably higher than that of the protrusions 3A. On the inner periphery side, the ratio of the surface porosity of the recesses to that of the protrusions is preferably 1.01 or more and 2.00 or less. As with the outer periphery, it is important not only to improve the porosity of the entire inner surface of the membrane, but also to shift the surface used for filtration over time from the recesses, which have higher porosity, to the protrusions, which have relatively lower porosity, without the membrane surface being used for filtration at the same time. From the same viewpoint, the ratio of the surface porosity of the recesses to that of the protrusions in the inner periphery is more preferably 1.02 or more and 1.80 or less, and even more preferably 1.02 or more and 1.50 or less.

[0047] In the porous hollow fiber membrane of this embodiment, it is preferable that the proportion of the recesses in the entire outer peripheral surface is as large as possible within a range that does not impair the abrasion resistance in the outer peripheral portion. By increasing the proportion of the recesses, the pore ratio becomes higher, and therefore higher water permeability and abrasion resistance can be exhibited. In addition, it is also preferable from the viewpoint of drying resistance that the moisturizing agent is easily retained in the recesses having a higher pore ratio (i.e., a larger number of holes) that are easily dried. The proportion of the recesses to the entire outer peripheral surface varies depending on the number of recesses and the height and width of the recesses. The proportion of the recesses to the entire outer peripheral surface is preferably 5% to 90%, more preferably 10% to 80%, and even more preferably 15% to 70%.

[0048] The average pore size and maximum pore size of the porous hollow fiber membrane of this embodiment are preferably 0.01 to 10 μm. If the average pore size and maximum pore size are 0.01 μm or more, the filtration resistance of the membrane is low and sufficient water permeability is obtained, and if they are 10 μm or less, a membrane with excellent separation performance is obtained. From the same viewpoint, the average pore size and maximum pore size of the porous hollow fiber membrane are more preferably 0.02 μm to 5 μm, and even more preferably 0.05 to 1 μm. If the average pore size and maximum pore size are 0.05 μm or more, it is preferable to measure the average pore size and maximum pore size by the method described in ASTM F:316-86. If the average pore size is smaller than 0.05 μm and high pressure is required for measurement, deformation of the membrane due to high pressure becomes a problem, so that it can be measured by filtering an indicator substance with a known particle size, and taking the particle size of the indicator substance with a rejection rate of 50% as the average pore size and the particle size of the indicator substance with a rejection rate of 1% as the maximum pore size.

[0049] In addition, in the porous hollow fiber membrane of this embodiment, the value obtained by dividing the maximum pore size by the average pore size is preferably 2.0 or less. The value obtained by dividing the maximum pore size by the average pore size is an index representing the uniformity of the pore size of the membrane, and the closer this value is to 1, the more uniform the pores of the membrane will be. When the ratio of the surface pore size of the recessed portion and the protruding portion described above increases, the value obtained by dividing the maximum pore size by the average pore size described below also increases. This is because the pore size distribution of the entire membrane becomes wider due to the change in the pore size distribution of each of the recessed portion and the protruding portion. If the value obtained by dividing the maximum pore size by the average pore size is 2.0 or less, high blocking performance can be achieved. From the same viewpoint, the value obtained by dividing the maximum pore size by the average pore size is more preferably 1.9 or less, and even more preferably 1.8 or less.

[0050] In the inner periphery of the porous hollow fiber membrane of this embodiment, the inner diameter XR (FIG. 1) connecting the protrusions 4A is preferably 0.1 mm to 5 mm. If the inner diameter is 0.1 mm or more, it is possible to suppress the pressure loss generated when the filtrate water flows through the hollow part, and if it is 5 mm or less, it is possible to increase the membrane packing density per unit volume and make it compact. It is more preferably 0.3 mm to 4 mm, and even more preferably 0.5 mm to 3 mm.

[0051] The membrane thickness of the porous hollow fiber membrane of this embodiment is preferably 0.05 mm to 2 mm. Here, the membrane thickness is expressed as membrane thickness=(recess outer diameter-recess inner diameter) / 2. If the membrane thickness is 0.05 mm or more, sufficient compressive strength and burst strength are obtained. If the membrane thickness is 2 mm or less, the membrane packing density per unit volume can be increased, and compactification is possible. From the same viewpoint, the membrane thickness is more preferably 0.1 mm or more and 1 mm or less.

[0052] The breaking elongation of the porous hollow fiber membrane of the present embodiment is preferably 30% or more. If the breaking elongation is 30% or more, the membrane has sufficient durability against physical cleaning such as air scrubbing. From the same viewpoint, the breaking elongation is more preferably 50% or more.

[0053] Next, an example of a preferred method for producing the porous hollow fiber membrane according to this embodiment will be described. The organic liquid to be used is one that is a potential solvent for the thermoplastic resin used in the present application. In the present application, a potential solvent refers to a solvent that hardly dissolves the thermoplastic resin at room temperature (25°C) but can dissolve the thermoplastic resin at a temperature higher than room temperature. It is sufficient that the solvent is liquid at the melt-kneading temperature with the thermoplastic resin, and it is not necessarily required that the solvent is liquid at room temperature.

[0054] When the thermoplastic resin is polyethylene, examples of the organic liquid include phthalate esters such as dibutyl phthalate, diheptyl phthalate, dioctyl phthalate, di(2-ethylhexyl) phthalate, diisodecyl phthalate, ditridecyl phthalate, etc.; sebacate esters such as dibutyl sebacate; adipate esters such as dioctyl adipate; trimellitate esters such as trioctyl trimellitate; phosphate esters such as tributyl phosphate, trioctyl phosphate, etc.; glycerin esters such as propylene glycol dicaprate, propylene glycol dioleate, etc.; paraffins such as liquid paraffin; and mixtures thereof.

[0055] When the thermoplastic resin is polyvinylidene fluoride, examples of the organic liquid include phthalate esters such as dimethyl phthalate, diethyl phthalate, dibutyl phthalate, dicyclohexyl phthalate, diheptyl phthalate, dioctyl phthalate, and di(2-ethylhexyl) phthalate; sebacate esters such as dibutyl sebacate; adipate esters such as dioctyl adipate; benzoate esters such as methyl benzoate and ethyl benzoate; phosphate esters such as triphenyl phosphate, tributyl phosphate, and tricresyl phosphate; ketones such as γ-butyrolactone, ethylene carbonate, propylene carbonate, cyclohexanone, acetophenone, and isophorone; and mixtures thereof.

[0056] The thermoplastic resin may be particles obtained by adjusting the particle size by crushing and / or grinding pellets or granular thermoplastic resin. Means for crushing and / or grinding pellets or granular thermoplastic resin include a multi-stage grinding method in which pellets are coarsely ground and then finely ground, and a method in which fine grinding is performed in one stage, but the method is not limited thereto. If the particles after grinding do not reach a predetermined particle size even with a fine grinder, they may be ground with an ultra-fine grinder capable of further fine grinding. Specific grinding means include grinding means using a hammer mill, turbo mill, jet mill, pin mill, centrifugal mill, rotoplex, pulverizer, wet grinding, chopper mill, ultra rotor, etc., and a room temperature or freeze grinding method can be used. For example, it is preferable to use a freeze grinding method for vinylidene fluoride resins that have a low glass transition point of about -35°C.

[0057] In order to obtain particles in a specified particle size range, classification is performed using an appropriate classifier. When obtaining particles in a specified particle size range from the classified particles, the particles may be further classified using another classifier, fine powders below the specified particle size may be removed, and the remaining particles (medium powder) may be used as the product. After classification, particles in a range larger than the target particle size range may be crushed again to obtain particles in the specified particle size range. Devices used for classification include vibrating sieves, inertial airflow classifiers, rotary blade classifiers, etc., and are not particularly limited.

[0058] In the case of mixing two kinds of polymers, each polymer may be pulverized and then mixed using a mixer. Classification may be performed after pulverization or after mixing, and is not particularly limited.

[0059] The particle size distribution of the particles after pulverization can be measured using a laser diffraction, scattering type particle size distribution measuring device. The particles whose particle size has been adjusted by crushing and / or pulverization preferably have a volume-based median diameter (D50 particle diameter) obtained from particle size distribution in the range of 50 to 500 μm, more preferably 70 to 400 μm. If the diameter is 50 μm or more, the particles can be stably charged without causing poor bite into the screw when being charged, for example, during melt kneading in an extruder or the like. If the diameter is 500 μm or less, a porous film can be stably produced without causing poor dissolution. In this specification, the D10 particle size, D50 particle size, and D90 particle size refer to values ​​measured using a laser diffraction particle size measuring device.

[0060] Examples of inorganic fine powders include silica, alumina, titanium oxide, zirconia oxide, calcium carbonate, etc., and particularly, fine silica having an average primary particle size of 3 nm to 500 nm is preferred. More preferably, it is 5 nm to 100 nm. Hydrophobic silica fine powder that is less likely to aggregate and has good dispersibility is more preferred, and even more preferably, hydrophobic silica with a MW (methanol wettability) value of 30 volume % or more is preferred. The MW value here is the volume % value of methanol that completely wets the powder. Specifically, the MW value is determined by adding silica to pure water, adding methanol below the liquid surface while stirring, and calculating the volume % of methanol in the aqueous solution at the time when 50 mass % of the silica has settled.

[0061] The amount of inorganic fine powder added is preferably 5% by mass or more and 40% by mass or less, in terms of the mass ratio of the inorganic fine powder in the molten kneaded product. If the ratio of the inorganic fine powder is 5% by mass or more, the effect of kneading the inorganic fine powder can be fully exhibited, and if it is 40% by mass or less, stable spinning can be achieved.

[0062] The mixing ratio in the melt kneading is preferably such that the volume ratio, calculated by dividing the mass by the specific gravity, is in the range of 15% by volume to 50% by volume for the thermoplastic resin and in the range of 50% by volume to 85% by volume for the total of the organic liquid and the inorganic fine powder, from the viewpoint of the balance between the water permeability and strength of the resulting hollow fiber and the stability of the spinning operation, which is a melt extrusion operation. The thermoplastic resin is preferably 15% by volume or more, from the viewpoint of the strength and spinning stability of the resulting porous multilayer hollow fiber membrane. Also, from the viewpoint of the water permeability and spinning stability of the resulting porous multilayer hollow fiber membrane, it is preferably 85% by volume or less.

[0063] The addition of inorganic fine powders has the following three advantages: (1) Surprisingly, by discharging a molten mixture containing inorganic fine powder from a spinneret to obtain a porous hollow fiber membrane, the surface openness of the recessed portion of the outer surface is significantly improved compared to the outer surface of a normal circular hollow fiber membrane. Although the reason for this is unclear, it is speculated that the presence of inorganic fine powder in the recessed portion, i.e., in the outer surface of the region where the center of curvature is outside the outer periphery of the porous hollow fiber membrane, contributes to the improvement in openness. (2) Due to the thickening effect of the inorganic fine powder, it is easy to obtain a film with an isotropic three-dimensional network structure, which results in high mechanical strength. (3) When producing a porous hollow fiber membrane as in the present embodiment, it is extremely difficult to obtain a porous hollow fiber membrane having sufficient concave and convex portions on both the outer and inner peripheries because the molding stability is greatly reduced as the height and number of concave and convex portions increases, but the addition of inorganic fine powder increases the viscosity of the molten mixture and significantly improves molding stability. As a result, a porous hollow fiber membrane having a large proportion of concave portions on the outer and inner peripheries of the membrane can be obtained.

[0064] The viscosity of the molten mixture when extruded is preferably in the range of 1 Pa·sec to 1000 Pa·sec. If it is 1 Pa·sec or more, the desired uneven shape can be obtained with high accuracy, and if it is 100 Pa·sec or less, the molten mixture can be stably extruded. A method for improving the viscosity is preferably to add inorganic fine powder to the molten mixture. Usually, in order to increase the viscosity, the polymer concentration is increased or a polymer with a high molecular weight is used, but the former reduces the porosity that contributes to filtration, and the latter is prone to problems such as molding defects. By adding inorganic fine powder, the viscosity of the molten mixture can be improved without restrictions on the molecular weight or concentration of the polymer, and deformation of the uneven shape can be suppressed in the idling part from extrusion from the spinneret to cooling, resulting in a stable porous hollow fiber membrane. The viscosity at the time of extrusion can be obtained by using a capillograph to measure the shear rate (shear rate) when actually extruding from the spinneret. The viscosity of the molten mixture when discharged is more preferably from 2 Pa·sec to 800 Pa·sec, and further preferably from 5 Pa·sec to 600 Pa·sec.

[0065] The mixing ratio in melt kneading is preferably such that the volume ratio, calculated by dividing the mass by the specific gravity, is in the range of 15% by volume to 50% by volume for the thermoplastic resin and 50% by volume to 85% by volume for the total of the organic liquid and inorganic fine powder, from the viewpoint of the balance between the water permeability and strength of the resulting hollow fiber and the stability of the spinning operation, which is a melt extrusion operation. From the viewpoint of the strength and spinning stability of the resulting porous hollow fiber membrane, the thermoplastic resin is preferably 15% by volume or more. Also, from the viewpoint of the water permeability and spinning stability of the resulting porous hollow fiber membrane, the thermoplastic resin is preferably 50% by volume or less.

[0066] The thermoplastic resin, organic liquid and inorganic fine powder can be melt-kneaded by using a conventional melt-kneading means, for example, a twin-screw extruder.

[0067] A mixture of a thermoplastic resin such as polyvinylidene fluoride and an organic liquid, or a mixture of a thermoplastic resin such as polyvinylidene fluoride, an organic liquid and an inorganic fine powder can be obtained by mixing using a Henschel mixer, a Banbury mixer, a Plosser mixer or the like. When mixing three components, namely, a thermoplastic resin such as polyvinylidene fluoride, an organic liquid, and an inorganic fine powder, it is advantageous in terms of improving melt moldability and the porosity and mechanical strength of the resulting porous film to first mix the inorganic fine powder with the organic liquid to allow the inorganic fine powder to fully adsorb the organic liquid, and then blend and mix the thermoplastic resin such as polyvinylidene fluoride, rather than mixing the three components simultaneously. The thermoplastic resin such as polyvinylidene fluoride and the organic liquid may be separately fed directly to a melt kneading extrusion device such as a twin-screw extruder without pre-mixing with a Henschel mixer, etc. In order to improve the kneading properties, the mixture may be melt-kneaded once after mixing to form pellets, and the pellets may be fed to a melt kneading extrusion device, extruded into hollow fibers, and cooled and solidified to form hollow fibers.

[0068] The mixture can be melt-kneaded using a normal melt-kneading means, for example, an extruder. Although the case where an extruder is used will be described below, the melt-kneading means is not limited to an extruder. An example of a manufacturing apparatus used to carry out the manufacturing method of this embodiment is shown in FIG. 6.

[0069] 6 includes an extruder 10, a hollow fiber forming nozzle 20, a coagulation bath 30 in which a solution for coagulating the membrane-forming stock solution is stored, and a plurality of rollers 50 for transporting and winding up the porous hollow fiber membrane 40. The space S shown in FIG. 6 is an empty space through which the membrane-forming stock solution discharged from the hollow fiber forming nozzle 20 passes before reaching the solution in the coagulation bath 30.

[0070] The molten mixture is extruded by the extruder 10 through the hollow fiber forming nozzle 20, which is attached to the tip of the extruder 10 and has one or more annular discharge ports arranged in a concentric manner. When producing a membrane with a multilayer structure, there is a method in which a hollow fiber forming nozzle 20 having two or more annular discharge ports is attached to the tip of the extruder 10, and the molten mixture is supplied from different extruders 10 to each annular discharge port and extruded, or a method in which one layer of the multilayer structure is produced and then the remaining layers are coated. For example, in the former method of production using different extruders, the molten mixtures supplied are merged at the discharge ports and overlapped to obtain a hollow fiber extrudate having a multilayer structure. At this time, by extruding molten mixtures having different compositions from adjacent annular discharge ports, a multilayer membrane in which the pore sizes of adjacent layers are different can be obtained. The different compositions refer to the case where the constituent substances of the molten mixture are different, or the case where the constituent substances are the same but have different composition ratios. Even if the thermoplastic resins are the same type, if they have clearly different molecular weights or molecular weight distributions, they are considered to have different constituent substances. The joining position of the molten mixtures having different compositions may be at the lower end surface of the hollow fiber forming nozzle 20 or may be at a position other than the lower end surface of the hollow fiber forming nozzle 20.

[0071] The shape of the discharge port of the hollow fiber molding nozzle 20 is not particularly limited as long as it has an unevenness on the outer and inner peripheries of the hollow fiber porous membrane. In other words, it is not particularly limited as long as the outer and inner peripheries of the discharge port are uneven.

[0072] The temperature at which the molten mixture is discharged is preferably 200°C to 270°C. If the temperature is 200°C or higher, the temperature of the fluid that forms the hollow portion can be increased, and the surface openness of the recesses on the inner surface side can be increased. Although the reason for this is unclear, it is assumed that the recesses are sandwiched between adjacent protrusions, so the temperature rises slightly, increasing the amount of solvent that evaporates, and improving the surface openness of the recesses.

[0073] The pressure at the tip of the hollow fiber forming nozzle when discharging the molten mixture is preferably 100 kPa or more and 900 kPa or less. In normal spinning, the shape of the hollow fiber forming nozzle having unevenness at the tip of the spinneret determines the shape of the hollow fiber membrane, but if the pressure at the tip is insufficient, the resin is not sufficiently distributed to the uneven parts of the nozzle (especially the parts that become the hollow fiber convex parts). In this case, as a result, only small unevenness is imparted to the hollow fiber membrane compared to the uneven shape of the spinneret discharge nozzle. That is, the concave parts are shallow, the convex parts are low, and the tops of the convex parts and the bottoms of the concave parts are likely to contact each other at the outer periphery of the membrane. Although the actual calculation of the pressure loss at the discharge tip is complicated, within the scope of the present invention, as described in the examples, it is preferable to use a value calculated simply from the equivalent diameter of the annular flow path, the flow rate at the time of discharge, and the melt viscosity of the resin. If the pressure at the nozzle tip is 100 kPa or more, it is preferable to form a suitable uneven shape in which the bottom of the concave part does not come into contact with the top of the convex part when the films are brought into closest contact with each other. If the pressure is 900 kPa or less, surface roughness (melt fracture) and reduction in elongation do not occur during spinning, and stable spinning can be achieved. The pressure at the tip is more preferably 150 kPa or more and 800 kPa or less, and even more preferably 200 kPa or more and 600 kPa or less.

[0074] The free-running time from when the molten mixture is discharged from the hollow fiber molding nozzle 20 until it solidifies in the cooling tank 30 may be set arbitrarily in order to adjust the pore size of the membrane, but a time of about 0.1 to 2 seconds is preferable because the membrane obtained by sufficient phase separation has sufficient pores. Generally, in the thermally induced phase separation method and the non-solvent phase separation method in which silica is not added, the viscosity of the discharged material is low, so that if the free-running time is extended, the unevenness disappears, but the addition of silica makes it possible to stably produce a hollow fiber membrane with an uneven shape.

[0075] In addition, in the free-running section S between when the material is discharged from the discharge port 20 and when it is immersed in the cooling tank 30, it is preferable to apply cooling air perpendicular to the discharge direction in order to improve the surface openness of the recesses. Although the reason for this is unclear, it is presumed that the reason for the high openness is that by applying cooling air perpendicular to the discharge direction, air accumulates in the recesses, suppressing evaporation of the solvent, or the wind does not directly hit the recesses, making it less likely for the holes on the surface to become clogged.

[0076] The hollow fiber-shaped molten kneaded material extruded from the discharge port 20 is cooled and solidified by passing through a coolant such as air or water, and is wound up on a skein or the like (corresponding to a winding roller 50 in FIG. 6) as necessary. During this cooling, thermally induced phase separation of the hollow fiber-shaped material is induced. In the hollow fiber-shaped material after cooling and solidification, a polymer-rich phase and an organic liquid-rich phase are finely separated and exist. In addition, if inorganic fine powder is contained and the inorganic fine powder is fine silica, the fine silica is unevenly distributed in the organic liquid-rich phase. By extracting and removing the organic liquid from this cooled and solidified hollow fiber-shaped material, the organic liquid-rich phase portion becomes a pore. Thus, a porous hollow fiber membrane can be obtained. In addition, it is preferable to extract and remove the inorganic fine powder from the viewpoint of further improving the water permeability of the obtained membrane.

[0077] The organic liquid and inorganic fine powder can be extracted and removed simultaneously if they can be extracted and removed with the same solvent. Usually, they are extracted and removed separately.

[0078] The organic liquid is extracted and removed using a liquid suitable for extraction that does not dissolve or denature the thermoplastic resin used and is miscible with the organic liquid. Specifically, the liquid can be contacted by a technique such as immersion. The liquid is preferably volatile so that it can be easily removed from the hollow fiber membrane after extraction. Examples of the liquid include alcohols and methylene chloride. If the organic liquid is water-soluble, water can also be used as the extraction liquid.

[0079] The inorganic fine powder is usually extracted and removed using an aqueous liquid. For example, when the inorganic fine powder is silica, the inorganic fine powder is first contacted with an alkaline solution to convert the silica into a silicate, and then contacted with water to extract and remove the silicate.

[0080] It does not matter whether the organic liquid is extracted and removed first or the inorganic fine powder is extracted and removed first. When the organic liquid is immiscible with water, it is preferable to extract and remove the organic liquid first, and then extract and remove the inorganic fine powder. Since the organic liquid and the inorganic fine powder are usually mixed and coexist in the organic liquid thick partial phase, this is advantageous in that the inorganic fine powder can be extracted and removed smoothly.

[0081] In this manner, the organic liquid and inorganic fine powder are extracted and removed from the cooled and solidified hollow fiber extrudate, thereby obtaining a porous hollow fiber membrane.

[0082] The hollow fiber-like material after cooling and solidification can be suitably stretched in the longitudinal direction at any of the following stages: (i) before the extraction and removal of the organic liquid and inorganic fine powder, (ii) after the extraction and removal of the organic liquid and before the extraction and removal of the inorganic fine powder, (iii) after the extraction and removal of the inorganic fine powder and before the extraction and removal of the organic liquid, or (iv) after the extraction and removal of the organic liquid and inorganic fine powder. In general, when stretching a porous hollow fiber membrane in the longitudinal direction, if the breaking elongation of the hollow fiber membrane is low, it cannot be stretched to the desired stretching ratio and breaks, so the breaking elongation is also important when stretching to increase water permeability. The porous hollow fiber membrane obtained by the manufacturing method of the present application has a high breaking elongation and can be suitably stretched. The stretching improves the water permeability of the porous multilayer hollow fiber membrane and reduces the strength in the direction perpendicular to the longitudinal direction of the hollow fiber, i.e., the compression strength and burst strength. Therefore, the stretching ratio is more preferably 1.1 times or more and 3 times or less. The stretch ratio here refers to the value obtained by dividing the length of the hollow fiber after stretching by the length of the hollow fiber before stretching. For example, if a hollow fiber with a length of 10 cm is stretched to 20 cm, the stretch ratio is 2 times according to the following formula. 20cm÷10cm=2 If necessary, the stretched film may be heat-treated to increase its compressive strength. The heat-treatment temperature is usually set to a temperature equal to or lower than the melting point of the thermoplastic resin. In addition, a manufacturing method in which a porous support layer and / or a support such as a braided cord is laminated to the inner surface side of the porous hollow fiber membrane of the present invention in order to improve strength is also a preferred embodiment. The lamination method may be either co-extrusion, in which the layers are laminated in a molten state, or a method in which the layers are solidified and then coated.

[0083] The porous hollow fiber membrane obtained as described above is used in a hollow fiber membrane module, a filtration device to which this hollow fiber membrane module is attached, and for the treatment of various types of water to be treated by the filtration device. EXAMPLES

[0084] Hereinafter, the present embodiment will be described more specifically with reference to examples and comparative examples, but the present embodiment is not limited to these examples.

[0085] Example 1 A mixture of vinylidene fluoride homopolymer (Solef6010 manufactured by Solvay), di(2-ethylhexyl) phthalate (DEHP) (manufactured by C.G. Ester Corporation) and dibutyl phthalate (DBP) (manufactured by C.G. Ester Corporation) as an organic liquid, and fine silica (manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL-R972, primary particle size approximately 16 nm) as an inorganic fine powder was used, and a hollow fiber membrane was melt-extruded by an extruder using a nozzle for hollow fiber molding. The melt-kneaded product had a composition of vinylidene fluoride homopolymer: di(2-ethylhexyl) phthalate: dibutyl phthalate: fine silica = 40.0: 30.8: 6.2: 23.0 (mass ratio), and was extruded from a nozzle for hollow fiber molding with the dimensions in Table 1 at a discharge temperature of 240 ° C. using air as a fluid for forming a hollow portion. The hollow fiber-like molten kneaded material extruded at a discharge temperature of 240° C. was passed through the air for 0.60 seconds and then introduced into a coagulation bath filled with water at 30° C. It was taken up at a speed of 20 m / min, sandwiched between belts and stretched at a speed of 40 m / min, and then contracted at a speed of 30 m / min while being exposed to hot air set at 140° C., and wound into a skein. The obtained hollow fiber-like product was immersed in isopropyl alcohol to extract and remove di(2-ethylhexyl) phthalate and dibutyl phthalate, and then dried. It was then immersed in a 50% by mass aqueous solution of ethanol for 30 minutes, immersed in water for 30 minutes, and then immersed in a 20% by mass aqueous solution of sodium hydroxide at 70°C for 1 hour, and further repeatedly washed with water to extract and remove the fine silica, thereby obtaining a porous hollow fiber membrane sample. Table 1 shows the detailed composition and conditions of the porous hollow fiber membrane sample. The porous hollow fiber membrane sample obtained in Example 1 was immersed in a 50% by mass aqueous ethanol solution for 30 minutes, and then fractured with liquid nitrogen. The cross section perpendicular to the extension direction was observed using an electron microscope. The observed image is shown in FIG.

[0086] Example 2 Using different sizes of hollow fiber forming nozzles, porous hollow fiber membrane samples were obtained in the same manner as in Example 1. Table 1 shows the detailed compositions and conditions.

[0087] Example 3 Using different sizes of hollow fiber forming nozzles, porous hollow fiber membrane samples were obtained in the same manner as in Example 1. Table 1 shows the detailed compositions and conditions. Example 4 Vinylidene fluoride homopolymer (Kynar 740 manufactured by Arkema) was used as the thermoplastic resin. Pellet-shaped Kynar 740 was crushed using a Linrex Mill (manufactured by Hosokawa Micron Corporation) by the freeze crushing method. Sorting was performed using a vibrating sieve, and particles with openings of 355 μm or more were removed, and particles with openings of 53 μm or more were used as the product. The D50 particle size after crushing was 160 μm. Except for using this thermoplastic resin and setting the idle time to 1.2 seconds, a porous hollow fiber membrane sample was obtained in the same manner as in Example 1. Table 1 shows the detailed composition and conditions.

[0088] Example 5 A porous hollow fiber membrane sample was obtained in the same manner as in Example 1, except that vinylidene fluoride homopolymer (KFW1000 manufactured by Kureha Corporation) and a mixture of bis(2-ethylhexyl) adipate (DEHA) and dibutyl sebacate (DBS) were used as an organic liquid, and the composition of the molten mixture was vinylidene fluoride homopolymer:bis(2-ethylhexyl) adipate:dibutyl sebacate:fine silica powder = 40.0:18.5:18.5:23.0 (mass ratio). Table 1 shows the detailed composition and conditions.

[0089] Comparative Example 1 A hollow fiber forming nozzle without unevenness was used to obtain a porous hollow fiber membrane sample in the same manner as in Example 1. Table 1 shows the detailed composition and conditions.

[0090] Comparative Example 2 Using a hollow fiber forming nozzle having an uneven shape only on the outer periphery, a porous hollow fiber membrane sample was obtained in the same manner as in Example 1. Table 1 shows the detailed composition and conditions.

[0091] Comparative Example 3 Using different sizes of hollow fiber forming nozzles, porous hollow fiber membrane samples were obtained in the same manner as in Example 1. Table 1 shows the detailed compositions and conditions. Comparative Example 4 Using a hollow fiber forming nozzle in which the apex of the inner surface concave portion was not on the line connecting the apex of the outer surface convex portion and the center, a porous hollow fiber membrane sample was obtained in the same manner as in Example 1. Table 1 shows the detailed composition and conditions.

[0092] <Evaluation> The obtained porous hollow fiber membrane samples were subjected to the following evaluations. Unless otherwise specified, all evaluation measurements were performed at 25° C. The evaluation results are shown in Table 1.

[0093] (1) Measurement of the inner diameter (mm) of the inner peripheral convex part, the inner diameter (mm) of the inner peripheral concave part, the outer diameter (mm) of the outer peripheral convex part, and the outer diameter (mm) of the outer peripheral concave part of the porous hollow fiber membrane A sample of the porous hollow fiber membrane was thinly cut with a razor or the like in a direction perpendicular to the longitudinal direction of the membrane, and the inner diameter of the convex portion, the inner diameter of the concave portion, the outer diameter of the convex portion, and the outer diameter of the concave portion were measured using a microscope on a cross section perpendicular to the extending direction of the hollow fiber membrane. The outer diameter of the convex portion on the outer periphery is the diameter of a concentric circle connecting the convex portions on the outer periphery. The outer diameter of the concave portion on the outer periphery is the diameter of a concentric circle connecting the apexes of the concave portions on the outer periphery (the portions where the membrane thickness is the thinnest). The same applies to the inner diameter of the concave portion on the inner periphery and the inner diameter of the convex portion on the inner periphery.

[0094] (2) Measurement of the height H (μm), width W (μm) and number of grooves of the porous hollow fiber membrane, and confirmation of whether the top of the inner periphery of the protrusion is on the line connecting the top of the recess and the center of the hollow fiber membrane. A photograph was taken with a scanning electron microscope at an arbitrary magnification that clearly confirmed the shape of the unevenness of the outer periphery in a cross section perpendicular to the extension direction of the porous hollow membrane. On the photograph, the difference between the diameter of the inner diameter and the diameter of the concentric circle passing through the part with the thinnest film thickness (usually the apex of the concave portion) and the diameter of the concentric circle passing through the apex of the convex portion (the part with the thickest film thickness) was measured, and the height H of the unevenness was calculated using the following formula. The width of the unevenness was determined as the width of the convex portion at a position half the height H of the unevenness from the thinnest film thickness. The number of unevenness was determined by visually counting the number of unevenness (number of threads) by taking an image of the entire cross section of the membrane. The same was true for the inner periphery. In addition, a scanning electron microscope was used to confirm whether or not the apex of the convex portion on the inner periphery was present on the line connecting the apex of the concave portion on the outer periphery and the center of the hollow fiber membrane.

[0095] (3) Measurement of pure water permeability (L / m2 / hr) of porous hollow fiber membrane A sample of the porous hollow fiber membrane was immersed in a 50% by mass aqueous solution of ethanol for 30 minutes, and then immersed in water for 30 minutes to wet the hollow fiber membrane. One end of the wet hollow fiber membrane with a length of about 10 cm was sealed, a syringe needle was inserted into the hollow part of the other end, and pure water at 25°C was injected into the hollow part from the syringe needle at a pressure of 0.1 MPa. The amount of pure water permeating to the outer surface was measured, and the pure water permeation flux was determined by the following formula (4). Here, the effective membrane length refers to the net membrane length excluding the part where the syringe needle is inserted. In addition, the number of measurements was 10, and the average value was taken as the pure water permeation amount under each condition. Here, the arithmetic average value of the inner diameter of the convex part and the inner diameter of the concave part was used as the inner diameter of the membrane.

number

[0096] (4) Pore structure, porosity (%) of the concave and convex parts of the inner circumference of the porous hollow fiber membrane Using a HITACHI SU8000 series electron microscope, the surface of the inner periphery of the porous hollow fiber membrane was photographed at an accelerating voltage of 3 kV at a magnification that allowed the shape of 20 or more holes to be confirmed, and the pore structure was confirmed. Then, using the photographed image, for example, as described in International Publication No. 2001 / 53213, a transparent sheet was placed on top of the copy of the image, and the hole parts were filled in black using a black pen or the like, and then the transparent sheet was copied onto white paper, so that the hole parts were clearly distinguished as black and the non-hole parts as white. Then, using commercially available image analysis software Winroof2018 Ver4.23.1, binarization was performed using discriminant analysis. The pore opening rate was calculated by determining the area occupied by the binarized image obtained in this way.

[0097] (5) Compressive strength (MPa) One end of a sample of a porous hollow fiber membrane with a length of about 5 cm was sealed, and the other end was open to the atmosphere. Pure water at 40°C was applied to the outer surface by total filtration, and permeated water was discharged from the end open to the atmosphere. The applied pressure was increased in increments of 0.01 MPa from 0.1 MPa, and the pressure was maintained at each pressure for 15 seconds. During these 15 seconds, the permeated water coming out of the end open to the atmosphere was sampled. As the applied pressure increases, the absolute value of the amount of permeated water (weight) increases until the hollow part of the hollow fiber is crushed, but when the applied pressure exceeds the compression resistance of the hollow fiber, the hollow part is crushed and begins to be blocked, so the absolute value of the amount of permeated water decreases despite the increase in applied pressure. The applied pressure at which the absolute value of the amount of permeated water is maximized was determined as the compression resistance.

[0098] (7) Scratch resistance (%) Using a sample of a porous hollow fiber membrane, a membrane with a membrane area of ​​25 m was measured in the same manner as described in WO 2004 / 112944. 2 A negative pressure type hollow fiber membrane module was produced. That is, both ends of a plurality of porous hollow fiber membranes were adhesively fixed with urethane resin, and a cartridge head was adhesively fixed liquid-tight to the outer periphery of one end, and a lower ring was adhesively fixed liquid-tight to the outer periphery of the other end, to produce a cylindrical hollow fiber membrane module. The effective length between the filtration interface of the adhesive fixing layer on the cartridge head side and the lower ring side was 2000 mm. The diameter of the adhesive fixing layer on both ends of the hollow fiber was about 150 mm. In this manner, a negative pressure type hollow fiber membrane module was produced. The obtained hollow fiber membrane module was used and immersed in an activated sludge tank with a volume of 8 m3. In addition, factory wastewater with a BOD of 750 mg / L was used as raw water. The MLSS concentration in the activated sludge was constant at about 10 g / L. The water permeability was measured by creating negative pressure in the hollow part of the membrane with a suction pump and gradually increasing the water permeability using a full-flow filtration method, and measuring the limit of the water permeability at which the transmembrane pressure difference did not increase suddenly (exceeding 10 kPa / week at 25°C).

[0099] The above filtration operation is performed with a membrane aeration volume of 6 Nm 3The system was operated in cycles of filtration / backwashing while constantly aerating air for 10 min / hour. The filtration / backwashing time cycle was filtration / backwashing: 9 min / 1 min, and the backwashing flow rate during backwashing was the same as that during filtration. To promote abrasion, diatomaceous earth (manufactured by Chuo Silica: #600-H) was added to the activated sludge tank to a concentration of 1000 ppm, and the system was operated for about one month at a filtration rate of 0.5 m / day. The pure water permeability of the hollow fiber membrane with an effective length of 10 cm was measured before and after operation, and the abrasion resistance was calculated using the following formula.

number

[0100] (7) Water permeability A filtration module 11 as shown in FIG. 7 was created using a sample of a porous hollow fiber membrane. The filtration module 11 has an effective membrane length of 1 m and 300 hollow fibers, and the hollow fibers at both ends are sealed with an epoxy-based sealant 13. The upper end of the module has an open hollow part in the hollow fiber membrane, and the lower end has a sealed hollow part in the hollow fiber membrane. River water with a turbidity of 2 to 4 degrees was filtered from the outer surface side of the hollow fiber through the inlet 14 for raw water and air, and filtrate was obtained from the inner surface side of the upper end. The set flux (set flux (m / day) is the value obtained by dividing the filtration flow rate (m3 / day) by the outer surface area of ​​the membrane (m2)) was increased stepwise, and the flux just before the transmembrane pressure difference began to rise rapidly was set as the limit flux (m / day). A rapid rise in transmembrane pressure was judged based on a rate of increase of about 50 kPa / 5 days.

[0101] [Table 1]

[0102] The results in Table 1 show that when each sample of the porous hollow fiber membrane of the Examples was used, good results were obtained in all of the compressive strength, water permeability test and abrasion resistance. [Industrial Applicability]

[0103] According to the present invention, it is possible to obtain a porous hollow fiber membrane having abrasion resistance, high water permeability, and compressive strength suitable for treating liquids containing inorganic or organic substances. [Explanation of symbols]

[0104] 1 Porous hollow fiber membrane 3. Unevenness on the outer periphery 4. Unevenness of inner circumference 10 Extruder 20 Hollow fiber forming nozzle 30 Coagulation bath 40 Porous hollow fiber membrane 50 Lola

Claims

1. A substantially cylindrical porous hollow fiber membrane made of a thermoplastic resin, A porous hollow fiber membrane, characterized in that the outer and inner circumferential portions have a plurality of projections and recesses extending continuously in the longitudinal direction of the hollow fiber membrane, and the projections and recesses are alternately formed along the circumferential direction of the hollow fiber membrane.

2. 2. The porous hollow fiber membrane according to claim 1, wherein the apex of the convex portion of the inner peripheral portion is located on a line connecting the apex of the concave portion of the outer peripheral portion and the center of the hollow fiber membrane.

3. 3. The porous hollow fiber membrane according to claim 1 or 2, characterized in that a ratio of the height of the projections and recesses of the outer circumferential portion to the height of the projections and recesses of the inner circumferential portion (height of the projections and recesses of the outer circumferential portion / height of the projections and recesses of the inner circumferential portion) is 1.0 or more and 20 or less.

4. 3. The porous hollow fiber membrane according to claim 1, wherein a ratio of an inner diameter / 2 of the recesses in the inner circumferential portion to an unevenness height of the inner circumferential portion (inner diameter of the recesses / unevenness height×100%) is 1.0 to 33%.

5. The porous hollow fiber membrane according to claim 1 or 2, characterized in that the height of the projections and recesses of the inner peripheral portion is 1 to 110 μm, and the height of the projections and recesses of the outer peripheral portion is 1 to 320 μm.

6. The porous hollow fiber membrane according to claim 1 or 2, characterized in that the width of the irregularities in the outer circumferential portion is 1 to 500 μm.

7. 3. The porous hollow fiber membrane according to claim 1, wherein the width of the projections and recesses on the inner periphery is 1 to 500 μm.

8. 3. The porous hollow fiber membrane according to claim 1, wherein a value obtained by dividing a surface porosity of concave portions of the inner circumferential portion by a surface porosity of convex portions of the inner circumferential portion is 1.01 to 2.

00.

9. 3. The porous hollow fiber membrane according to claim 1, wherein the outer peripheral portion and the inner peripheral portion have 1 to 200 grooves in the circumferential direction of the hollow fiber membrane.

10. 3. The porous hollow fiber membrane according to claim 1, wherein the thermoplastic resin contains a fluororesin or a polyolefin resin as a main component.

11. The porous hollow fiber membrane according to claim 10, characterized in that the fluororesin comprises at least one selected from the group consisting of polyvinylidene fluoride resin (PVDF), chlorotrifluoroethylene resin, tetrafluoroethylene resin, ethylene-tetrafluoroethylene copolymer (ETFE), ethylene-monochlorotrifluoroethylene copolymer (ECTFE), hexafluoropropylene resin, and mixtures of these resins.

Citation Information

Patent Citations

  • Hollow yarn type permeating device

    JP1982194007A

  • Method for backwashing hollow yarn membrane filter

    JP1985019002A

  • Reinforced collapsible ladder

    WO2010063772A1